Lungs on fire. (27th June 2013) - Batra, Sandeep; Vaid, A K; Bhargava, Rahul; Gupta, Sachin
Abstract : A 50-year-old man was diagnosed as classical Hodgkin's lymphoma stage III B. He had been a reformed smoker and has had a coronary artery disease as his comorbidity. He was started on adriamycin, bleomycin, vinblastine, dacarbazine (ABVD)-based chemotherapy. An interim disease evaluation was suggestive of metabolic complete response after four cycles of ABVD. After completion of his sixth cycle, he presented with low-grade fever, dry cough, generalised malaise and increasing dyspnoea on exertion. FDG (18 fluoro-deoxyglucose) positron emission tomography (PET)-CT revealed intensely FDG avid diffuse activity in mid and lower zone both lung fields. He was started on intravenous steroids along with broad spectrum antibiotic and antifungal cover. Clinical, radiological and laboratory assays did not reveal any infective pathology. He was diagnosed as bleomycin-induced pulmonary toxicity (BIP). Despite best supportive care, his pulmonary functions deteriorated and he developed cardiac arrhythmias. He finally succumbed to the irreversible chemotherapy toxicity of a curable malignancy.